Student-Centered Approach in Higher Education to Transform Learning in India – A New ISL Model (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: The purpose of this scholarly paper, "Student-Centered Approach in Higher Education to Transform Learning in India – A New ISL Model", is to conceptualize and propose an innovative educational framework—Integrated Super Learning (ISL) Model—that holistically enhances student development by unifying three critical dimensions: confidence boosting through skill-based learning, maturity development through ethical and value-based education, and competency building through technology and research integration. Grounded in both conceptual and analytical methodologies, the paper aims to fill the existing gaps in fragmented student-centered learning models by offering a comprehensive, scalable, and contextually relevant solution for Indian higher education institutions. Methodology: This study employs an exploratory research design, integrating conceptual and analytical frameworks to propose and validate the new Integrated Super Learning (ISL) model aimed at transforming student-centered learning in Indian higher education. The proposed model is analysed using appropriate analysis frameworks. Results/Analysis: The paper employs qualitative methods, including an extensive literature review and stakeholder consultations, to develop and validate the Integrated Super Learning (ISL) Model. To evaluate the feasibility and practicality of the ISL framework, two strategic tools are applied (1) SWOC Analysis (Strengths, Weaknesses, Opportunities, Challenges) – This is used to assess the internal and external factors that influence the implementation and effectiveness of the ISL model from institutional and academic standpoints. (2) ABCD Analysis (Advantages, Benefits, Constraints, Disadvantages) – framework provides a balanced examination of the ISL model’s holistic value and limitations in real-world educational environments.Originality/Value: The innovative educational framework—Integrated Super Learning (ISL) Model—that holistically enhances student development by unifying three critical dimensions: confidence boosting through skill-based learning, maturity development through ethical and value-based education, and competency building through technology and research integration. The analyses provide a comprehensive, evidence-based understanding of the model’s applicability in the Indian higher education system, highlighting both its transformative potential and practical challenges.Type of Paper: Exploratory, model based qualitative Analysis.
Keywords: Student-Centered Learning; Higher Education; ISL Model; Confidence Building; Maturity Development; Competency Building; India